Guiguinto Garden School a horticultural learning complex - Santos, Anne Claudia U.; Perion, Sharon S. (Quezon City College of Architecture, University of the Philippines Diliman, 2019)
The country is brimming with unique and diverse species of flowering plants. In the 1990s, the local Horticulture industry gave promising results as exports and revenues increased and contributed greatly to the economy. As problems started to arise in the agricultural farming sector, the government started to focus more on ensuring food security and removed horticulture as one of the listed priorities of the government. Currently, the horticultural sector is calling out to the government to reconsider this in order to further develop the industry as a potential contributor in the country's economy and tourism. Because of the lack of importance and awareness to the field, majority do not realize its full potential as an industry, as a science, as a source of energy in terms of food production, and lastly, as a social science -- on how horticulture improves and affects how people live and appreciate the urban environment they are inhabiting. Through research and data gathering through ocular visits of local horticultural facilities and interviews with professionals in the field, the researcher narrows down issues and analysed these data into coming up with a learning facility that aids in spreading awareness and empowering the industry and the craft. The proposed development of a learning complex facility is free for anyone to enrol -- from students, hobbyists to professionals, with or without background on horticulture. This learning facility will provide from courses in techniques in horticulture cultivation, its production, and to managing and marketing these products as a source of income. This complex integrates traditional and modern technologies in plant cultivation into the built urban environment while also providing basic garden needs. With the micro-climate conditions in Bulacan, the existing garden industry in Guiguinto, and their proposed Planned Unit Development entitled The Garden City Growth Node, the project development will then be theoretically integrated into this complex with the cooperation of the local government unit of Guiguinto and partnerships with local horticultural and plant organizations. This study will determine and focus on the current conditions of the horticultural industry through considerations of Guiguinto as a site and community, and designing an educational facility that will complement the existing industry as it establishes as a stepping stone for its further developments in education, tourism, research, and technology.
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Horticulture; Horticultural industry; Horticultural industry -- Design